THE CREATIVE ECONOMIC DEVELOPMENT IN IMPROVING THE INCOME OF WOOD ARTISTS - Siti Mariam; Pramudi Harsono; Irwan Sukmawan; Tabroni Tabroni (International Journal of Economy, Education and Entrepreneurship, 2023)
Creative economy development plays a role in a country's economy, especially in income generation, job creation, export revenue, technology, intellectual property, and other social roles. This study aims to find out how the role of the creative economy increases the income of wood artisans. This type of research is field research, while the nature of this research is descriptive and qualitative with data collection techniques using interviews and documentation. And all these data were analyzed by induction. The results obtained from this study are that the development of the creative economy carried out by wood artisans is to continue to improve innovations that consumers want so that other artisans do not abandon their products. Increased creativity and innovation by artisans increase the interests of consumers and affect the income received by artisans. The development of the role of the creative economy influences the increasing the business income of the wood artisans